Advances in Corrosion Mitigation for Waste-to-Energy Systems: Evaluating Coatings and Application Techniques - Bourtsalas, Athanasios; Yan, Dianyi (Technical Annals, 2023)
Waste-to-Energy (WTE) systems, utilizing post-recycled municipal solid waste (MSW) and other biomass materials, are proven alternatives to landfilling for sustainable waste management. These processes offer benefits such as reduced landfill space, decreased methane emissions, and minimized waste volume. However, operational challenges, specifically high-temperature corrosion (HTC) of superheater tubes, hinder their efficiency due to the presence of chlorine, alkaline salts, and sulfates. To address this issue, a range of coating techniques have been developed, with thermal spray techniques, particularly high velocity oxy-fuel (HVOF) spray, proving the most effective for protecting superheater tubes. A comparative analysis of experimental data from multiple studies indicates that coatings with Alloy 625, Alloy C-276, Colmonoy 88, FeCr, IN625, NiCr, NiCrTi, and A625 offer high corrosion resistance at relatively low material costs, with corrosion rates below 1 mm/year. High chromium, nickel, and molybdenum content coatings perform exceptionally well under high-temperature and high-chlorine conditions. Notably, T92 and P91, due to their low cost and high corrosion resistance, are strong candidates for superheater tubes operating at 550°C. While A625 demonstrates excellent corrosion resistance, its high cost limits its practicality. Ultimately, the selection of suitable coatings depends on the specific WTE plant design and operating experience. The additional cost of applying these coatings is a minor fraction of the overall financial gains, as it extends the superheater tubes’ lifetime and reduces plant downtime for tube repair or replacement.